Metal films from a single source and their application in nanoporous filtration synthesis, electromagnetic interference shielding, and electroadhesion - Veerasubash, Muthupandi; Birajdar, Sarika Hanamant; Kika, Sharmin Percy; Senthilkumaran, Marimuthu; Deshpande, Karan; Shevate, Rahul; Krishnamoorthy, Kothandam (ACS Omega, 2026)
Electroless metal depositions are carried out by a series of reduction steps involving multiple metal ions to obtain a film on synthetic and natural substrates. Herein, we report the use of metal ions from a single element to deposit metal films on various substrates. In a typical metal deposition procedure, Pd2+ ions are anchored on a polycarbonate membrane with vertically aligned pores of 0.6 mu m, which was reduced to its nanoparticles by sodium borohydride. The Pd nanoparticle-modified membrane was then immersed in a Pd plating bath. The Pd2+ ions are reduced by the reducing agent present in the plating bath. The reaction is catalyzed by the Pd nanoparticles. The Pd-modified membrane with vertically aligned Pd tubes were used to convert p-nitrophenol to p-aminophenol, which is an important molecule in the production of acetaminophen. While filtering the reactants through the Pd tubes, due to increased collision between the reactants and the catalyst Pd tubes, 100% conversion is achieved within 5 min. On the contrary, the conversion is only 10% if the membrane is placed in a vessel comprising the reactants. Due to the versatile nature of the metal deposition procedure, nickel was deposited on cotton substrates by a similar procedure. The nickel film-coated cotton cloth showed an impressive electromagnetic shielding interference efficiency of -60 dB while the uncoated cotton cloth did not shield electromagnetic radiation. To demonstrate the versatility of the approach, Pd-coated synthetic polymeric substrates are used to electroadhere gels and gel-like substances. Nickel-coated substrates are not suitable for electroadhesion; hence, a conjugated polymer was deposited on the substrate to electroadhere gel-like substances.